2003
DOI: 10.1097/01.asn.0000070146.29445.d8
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Renal Dysfunction

Abstract: Abstract. The incidence rate of end-stage renal disease has increased in many countries in the past 20 yr, including the United States and Singapore. The increase in ESRD incidence in the United States is primarily attributable to diabetes and to hypertension. In Singapore the major cause of ESRD is diabetes, however the prevalence of hypertension in the Singapore population is rising rapidly, and renal complications of hypertension may become more common in the future. Information on the association of hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Several investigations have suggested that chronic kidney disease stage is an excellent measure of severity and an accurate predictor of the risk of comorbidity and complications (El Nahas and Bello 2005;Knight et al 2003;Levey et al 2003). Possible refinements to the classification scheme around several issues including the interaction of increasing age with glomerular filtration rate, the value of different disease severity predictors in different patient populations, and the basis of selection of glomerular filtration rate cut-off values for some disease stages are being researched (Jones 2003;Levey et al 2003Levey et al , 2005Obrador et al 2002).…”
Section: Classificationmentioning
confidence: 99%
“…Several investigations have suggested that chronic kidney disease stage is an excellent measure of severity and an accurate predictor of the risk of comorbidity and complications (El Nahas and Bello 2005;Knight et al 2003;Levey et al 2003). Possible refinements to the classification scheme around several issues including the interaction of increasing age with glomerular filtration rate, the value of different disease severity predictors in different patient populations, and the basis of selection of glomerular filtration rate cut-off values for some disease stages are being researched (Jones 2003;Levey et al 2003Levey et al , 2005Obrador et al 2002).…”
Section: Classificationmentioning
confidence: 99%
“…59 Thus, obese individuals have been found to have an increased renal plasma flow and increased glomerular filtration rates. 60 At the same time, abdominal obesity has also been associated with a decrease in glomerular filtration rates and an increase in albumin excretion.…”
Section: Renal Abnormalities In Obesity Hypertensionmentioning
confidence: 99%
“…hypertension; renal injury; kidney; glomerulus; chronic kidney disease HYPERTENSION IS ONE OF THE leading causes of chronic kidney disease (CKD) that affects nearly 20 million Americans (9,17). Despite effective medications, compliance and drug costs remain a problem, and only a small percentage of patients achieve adequate blood pressure control (9).…”
mentioning
confidence: 99%